Website-Based Student Achievement Book Using the Waterfall Method - Nourma Budiarti, Rizqi Putri; Fathin, A N; Sulistiyani, E (International Journal of Scientific Research and Management (IJSRM), 2022)
Al Qur'an Education Park (TPA) Al Badar has approximately thirty students, but that number will continue to grow. The recording of achievement cards is done manually, and everything is done by the Al-Badar TPA teacher. Usually, teachers record student learning outcomes using achievement cards, and achievement cards are filled out after students learn to read Iqro or the Qur'an and handed over to their students. However, amid the current COVID-19 pandemic, face-to-face meetings are very difficult, especially between teachers and participants who are undergoing online teaching. Based on the problems that occurred at the Al Badar TPA regarding the recording of student achievement and the importance of technology for education, it is necessary to have an information system at the Al Badar TPA. The method used in this research is the waterfall method approach in the manufacture of information systems with several stages, including problem identification, system requirements analysis, system design, system creation, and system testing, and also system analysis. In making the system, PHP and MySQL are used with the CodeIgniter framework. In system testing, the author uses two methods of black-box testing and white-box system testing. While the results of the analysis of the system in terms of testing the quality ofservice users, namely by using usability testing. The results of this study are a website-based student achievement book as an online learning achievement record book that can function well, both systemically and from the user's side of the application and greatly assists the needs of the Al-Badar TPA during the pandemic. The results obtained from the usability testing analysis are 90%, so it can conclude that the system is feasible and easy to use. So, a website-based student achievement book as book’s achievement record online can function properly and greatly help the needs of the TPA Al-Badar during the pandemic.